Disaster Mitigation and Simulation Education: Impact on Islamic Boarding School Students' Knowledge and Preparedness: Edukasi Melalui Mintigasi dan Simulasi Bencana Terhadap Pengetahuan dan Kesiapsiagaan Bencana Santri Pondok Pesantren - Kokoh Wahyu Prastyo; Nurul Hidayah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Islamic boarding schools are among the settings at risk for disaster-related casualties due to inadequate education and limited supporting facilities and infrastructure. Most Islamic boarding schools have densely populated buildings and electrical wiring installations that may increase the risk of short circuits and potentially trigger fires. In addition, the majority of students are between 13 and 18 years old, an age group considered vulnerable to becoming disaster victims. Considering the substantial risk of disasters occurring in Islamic boarding schools, disaster education is essential to improve students’ knowledge and preparedness in responding to disasters. Therefore, this study aimed to determine the levels of knowledge and preparedness among Islamic boarding school students before and after receiving disaster education through disaster mitigation and simulation programs. This study employed a quantitative research method with a pre-experimental design using a one-group pretest–posttest approach. The study population consisted of 342 Islamic boarding school students. The sampling technique used was cluster sampling, resulting in a total sample of 60 participants (n= 60). The inclusion criteria in this study were students who served as dormitory room leaders and members of the Islamic boarding school health unit committee. The statistical analysis was performed using the Wilcoxon signed-rank test. The results showed a significance value of 0.000 (p < 0.05), indicating a statistically significant difference in the levels of knowledge and preparedness among Islamic boarding school students before and after the implementation of disaster education and training. Disaster education through mitigation and simulation programs had a positive effect on improving students’ knowledge and preparedness in facing disaster situations.